2018
DOI: 10.1007/s11469-018-0024-4
|View full text |Cite
|
Sign up to set email alerts
|

Do Chinese and British University Students Use Smartphones Differently? A Cross-cultural Mixed Methods Study

Abstract: Although an increasing number of studies have focused on problematic smartphone use and smartphone addiction, few of these studies have employed both quantitative and qualitative methods or employed a cross-cultural design. A limited number of studies have compared eastern and western groups. The present study investigates the prevalence and causes of problematic smartphone use among Chinese and British undergraduates. A sample of n = 778 undergraduates participated in this study (475 Chinese students and 303 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 35 publications
6
36
0
Order By: Relevance
“…It could be speculated that the effect of protective factors such as high empathy or life satisfaction differ in both cultures, although works such as by Lachmann et al (2018) or older work by Melchers et al (2015) rather hint at the comparability of mechanisms. In general, the present review results are in line with the study by Yang et al (2019) comparing British and Chinese students; our findings emphasize differences regarding prevalence rates between cultures.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It could be speculated that the effect of protective factors such as high empathy or life satisfaction differ in both cultures, although works such as by Lachmann et al (2018) or older work by Melchers et al (2015) rather hint at the comparability of mechanisms. In general, the present review results are in line with the study by Yang et al (2019) comparing British and Chinese students; our findings emphasize differences regarding prevalence rates between cultures.…”
Section: Discussionsupporting
confidence: 91%
“…The specific uses of SNSs may be different between cultures. Furthermore, Asian users have been shown to display more SNUD symptoms than Western users (Kuss et al, 2014;Stodt et al, 2018;Yang et al, 2019). This shows that further research examining SNUD in Asian countries is warranted.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…One Thai study found that 45.8% of students aged 18-24 years in Chiang Mai had excessive smartphone use [29], while in Japan, Tateno and colleagues documented a smartphone addiction prevalence of 22.8% among males and 28% among female college students (mean age 19 years ±1.3) [30]. In Western countries, the prevalence of smartphone addiction and/or other problematic smartphone use ranged from 16.9% to 43.3% [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear whether smartphone use or PSU changes between school and university. The move to university entails major lifestyle changes and disruption to existing social support networks, as well as increased independence (Yang et al 2019b). Consequently, it would be useful to further investigate PSU among British young adults.…”
mentioning
confidence: 99%